Respuesta :
8x²-18x-56
Solve :
- (4x + 7) (2x - 8)
apply distributive method
- (4x)(2x)+(4x)(-8)+7(2x)+7(-8)
simplify the following
- 8x²-32x+14x-56
final outcome
- 8x²-18x-56
Answer:
B) [tex]8x^2-18x-56[/tex]
Step-by-step explanation:
Given expression:
[tex](4x + 7)(2x - 8)[/tex]
Apply the FOIL method: [tex](a+b)(c+d)=ac+ad+bc+bd[/tex]
[tex]\implies (4x \cdot 2x)+(4x \cdot -8)+(7 \cdot 2x) +(7 \cdot -8)[/tex]
[tex]\implies 8x^2-32x+14x-56[/tex]
Combine like terms:
[tex]\implies 8x^2-18x-56[/tex]